الدَّوْرُ التَّشْرِيعِيُّ للسُّلْطَةِ التَّنفِيذِيَّةِ فِي ظِلِّ الدُّسْتُورِ القَطَرِيّ- دِرَاسَة مُقَارنَة - آمنه محمد الخاطر (20352129) (2020)
The modern political systems have seen a significant retreat in the role of parliament, which led to the dominance of the executive power and its interference in the legislative domain. This research clarifies the important role of the executive power in the legislative scope and tools, reserved for law and regulations, in Qatar, France and Egypt. Moreover, it identifies the competent authorities that are practicing the legislative process in the executive power in accordance with the constitution and laws of each of these comparative countries. شهدت النُّظُم السِّيَاسِيَّة الحديثة تراجعًا كبيرًا لدور البرلمان، مما أدى إلى هيمنة السُّلْطَة التَّنفِيذِيَّة وتدخلها في المجال التَّشْرِيعِيّ، فتقوم هذه الرسالة على توضيح الدَّوْر المهم للسُّلْطَة التَّنفِيذِيَّة في العَمَلِيَّة التَّشْرِيعِيَّة من خلال تحديد المجال والأدوات التَّشْرِيعِيَّة المحجوزة للقَانُون واللَّوَائِح في دولة قطر وجُمْهُورِيَّة فرنسا وجُمْهُورِيَّة مصر العَرَبِيَّة. كما عملت على تحديد السُّلطَات المختصة التي تمارس العَمَلِيَّة التَّشْرِيعِيَّة على سلم السُّلْطَة التَّنفِيذِيَّة وفقًا لدستور كل دولة من الدول محل المقارنة وقَوَانِينها. Other Information Published in: QScience Connect License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.5339/connect.2020.4